Epidemiological study on chronic otitis media in school children in Bantul regency - Soenarto Sastrowijoto, Soenarto Sastrowijoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
An epidemiological study on Chronic Otitis Media (COM) in children in Bantu[ regency, especially its prevalence in relation to socioeconomic status and index ofachievement has been done. The study used two-step cluster random sampling. The subject of the study was 16 primary schools with 2896 children, taken out from 17 districts consisting of 514 primary schools with a total number of 90 000 children.The study was carried out for six months from May 1990, and the result showed that the prevalence of COM was 5.28%, consisting of 2.10% serous COM and 3.18% suppurative COM, and middle ear cholesteatoma was found in three of them. A number ofrisk factors, the educational level and job of the father, the mothers educational level, the economic status based on the value of their property, nutrition and tidiness, the status of children, and the size of the family were also studied.The resultof the study showed that the economic status (P <0.05) and the mothers educational level (P < 0.01) had a significant indirect relation to the prevalence of COM. The index of achievement of children in natural sciences, Indonesian language, and mathematics was not influenced by the serous COM, but was significantly (P < 0.01) influenced by the duplex suppurative COM.The study of increasing the mothers educational level, the economic status, and the managementofCOM cases by giving hearing aid or developing national program ofmicracar-sugeryservices are suggested.Key Words: chronic otitis media - school age children - middle ear cholesteatoma - index of achievement - micro-ear-surgery